Data for feasibility study on using combined tomography and spectroscopy techniques to evaluate the physical and chemical characteristics of organo-mineral fertilisers - Sakrabani, Ruben; Mosca, Sara; Liptak, Alexander; Burca, Genoveva (Cranfield University, 2025)
Fertilisers play a key role in agriculture, providing key nutrients needed by crops to ensure a secure food supply. However, with increasing prices and rising environmental concerns, there is a growing need to rely on alternative and sustainable fertiliser sources, introducing the opportunity to use organic amendments to formulate organo-mineral fertilisers (OMF). Despite their environmental advantages, the inherent variability in composition of organic amendments within OMF poses a challenge for their standardisation. This study aims to use OMF derived from anaerobic digestate and coupled with carbon capture technologies to analyse for its physical characteristics and chemical composition using neutron computed tomography (NCT), X-ray computed tomography (XCT) and Raman spectroscopy (RS). This work represents the first attempt to utilise a combination of imaging techniques to investigate on OMF and demonstrates their feasibility for measuring the variability between individual samples. This is a proof-of-concept study which shows that combining NCT and XCT can provide images on how uniformly packed each OMF pellet are. The use of RS is to characterise OMF is more challenging largely due to the high fluorescence background arising from its matrix. This study needs to be further developed to enable image-based analysis using machine learning algorithms to determine characteristics of large batches of OMF.
The dataset comprises spectra for Raman Spectroscopy and reconstructed images for X-Ray Computed Tomography and neutron computed tomography. **Please note, more data will be added here soon.**
Keywords: organo-mineral fertilisers; soil nutrients; Neutron computed tomography; Raman spectroscopy; X-ray computed tomography